BEYOND COMPLIANCE: DETERMINANTS OF ACCRUAL ACCOUNTING SUCCESS IN JAMBI GOVERNMENT - Naufal, Muhammad Dzakwan; Afrizal, Afrizal; Ridwan, Muhammad (Faculty of Economics and Business Universitas Jambi, 2026)
Despite achieving consecutive unqualified opinions, Jambi Province's persistent asset discrepancies and expenditure recording errors reveal that formal regulatory mandates in Indonesia have failed to guarantee substantive compliance in accrual-based government accounting. This study examines the key determinants of accrual-based government accounting standards implementation within the Jambi Provincial Government, focusing on human resources, infrastructure, and information technology. A survey was conducted involving 100 employees directly engaged in financial administration, reporting, budgeting, internal control, and information system management across regional government organizations. Data were collected between 22 September and 10 October 2025 to capture post-audit conditions and were analysed using multiple linear regression with SPSS 26. The findings indicate that human resources, infrastructure, and information technology simultaneously have a significant effect on accrual-based standards implementation. Partially, human resources and information technology exert significant positive influences, while infrastructure does not show a meaningful contribution. This study contributes to the literature by integrating empirical findings with institutional theory and resource-based theory, demonstrating that technological readiness and human resource quality serve as primary drivers of public sector accounting reform effectiveness beyond the mere availability of physical facilities.